Del Derecho de Acción a la efectiva Tutela Jurisdiccional de los Derechos - Priori Posada, Giovanni F. (2014)
Throughout the history of Procedural Law, a theme which undoubtedly calls for greater importance is the right of action, however, today does not have greater presence. Accordingly, the focus has moved towards the effective jurisdictional protection due to the phenomenon of constitutionalisation which the right of action has crossed. the author, in addition to analyzing the most important landmarks in the development of right of action, also focuses on the study of what is currently happening with effective judicial protection in order to reach a truly effective process thatensures our rights.